Modern Trends In The Reform Of The Legal Status Of Farms In Ukraine - MISINKEVYCH, Leonid; MISINKEVYCH, Anna (University Scientific Notes, 2023)
The article studies the legal problems of the functioning of farms in Ukraine as an independent legal institution of agrarian law. After the opening of the land market, the authors analyse the dynamics and statistics regarding the registration of the right of private ownership of farmland, which is on their balance sheet in the status of permanent use. In this vein, the norms of land and agrarian law and the legal mechanism for the realization of the acquisition of the right to private property through free privatization for farmers whose land is currently registered for permanent use are investigated. In addition, the article examines the newly adopted draft law № 6013 «On the peculiarities of the regulation of entrepreneurial activities of certain types of legal entities and their associations in the transition period» adopted in the first reading by the Verkhovna Rada and the explanatory note to it, which was developed by people’s deputies. This document is aimed at the destruction of cooperative legal relations in the conduct of agribusiness, by transforming all enterprises in Ukraine into corporate ones. In this regard, the authors express a number of comments that are unacceptable for farming in Ukraine. In this regard, the authors express a number of comments that are unacceptable for farming in Ukraine. In the scientific work, the scientists present legal and economic arguments, which claim that the above bill is devastating for small and medium-sized agribusiness in our country and does not correspond to the main legal dogmas of the European Green Course. According to the authors, the adoption of such a regulatory act will lead to the monopoly of agricultural holdings and the loss of the country’s agricultural potential both at the international and national levels. In this context, the foreign experience of farming operations in countries where corporate legal relations of business are a priority, for example, the United States of America and the European Union, is studied.